A quality improvement cycle for acute bronchospasm in primary health care: Mitchell's Plain Community Health Centre, Cape Town - Marimuthu, Sarojini (Department of Public Health and Family Medicine, 2015)
Asthma affects over 300 million people worldwide and is the sixth highest cause of morbidity and mortality in South Africa. Mitchell’s Plain is a large suburb in Cape Town, with a population of approximately 320 000 people. A previous study in 2006 indicated that 15.7% of patients that presented to Mitchell’s Plain Community Health Care casualty were for an acute exacerbation of asthma and 7.8% of total deaths were from acute asthma. There was generally poor adherence to the national guidelines with respect to the management of an acute asthma exacerbation. Aim and Objectives: This study aimed to assess and improve the quality of management of acute bronchospasm at Mitchell’s Plain CHC. Objectives included assessing the current management, comparing it to the national guidelines and implementing strategies to improve care. Method: The study methodology was that of an audit cycle. Eligible patients were identified from the casualty admissions register. A total of 351 patients’ records were reviewed and compared to criteria based on the national guidelines. The initial findings were presented to the casualty staff that critically reflected; planned and implemented change. Intervention strategies involved raising awareness about the asthma guidelines, the audit tool and the South African Triage Score. A re-audit was performed after 6 months.